New and known predictors of the postthrombotic syndrome: A subanalysis of the ATTRACT trial - Félix Rinfret; Chu‐Shu Gu; Suresh Vedantham; Susan R. Kahn (Research and Practice in Thrombosis and Haemostasis, 2022)
Abstract Introduction Postthrombotic syndrome (PTS) remains associated with significant clinical and economic burden. This study aimed to investigate known and novel predictors of the development of PTS in participants of the ATTRACT (Acute Venous Thrombosis: Thrombus Removal With Adjunctive Catheter‐Directed Thrombolysis) trial. Methods We used multivariable logistic regression to identify baseline and postbaseline factors that were predictive of the development of PTS during study follow‐up, as defined by a Villalta score of 5 or greater or the development of a venous ulcer from 6 to 24 months after enrollment. Results Among 691 patients in the study cohort (all had proximal deep vein thrombosis [DVT] that extended above the popliteal vein, of which 57% had iliofemoral DVT), 47% developed PTS. Further, we identified that Villalta score at baseline (odds ratio [OR], 1.09 [95% confidence interval [CI], 1.05–1.13] per one‐unit increase) and employment status (unemployed due to disability: OR, 3.31 [95% CI, 1.72–6.35] vs. employed more than 35 hours per week) were predictive of PTS. In terms of postbaseline predictors, leg pain severity at day 10 (OR, 1.28 [95% CI, 1.13–1.45] per 1‐point increase in a 7‐point scale) predicted PTS. Also, patients receiving rivaroxaban on day 10 following randomization had lower rates of PTS (OR, 0.53 [95% CI, 0.33–0.86]) than patients on warfarin. Conclusions Novel predictors for PTS identified in our study include baseline Villalta score, leg pain severity at 10 days, and unemployed due to disability. Our findings also suggest that the initial choice of anticoagulant to treat DVT may have an impact on the development of PTS.